Scenario Planning Approach to Enhance Business Competitiveness and Sustainable Growth in the Indonesian Midstream Gas Sector: A Case Study of PT Perta Daya Gas - Adikharisma, Revi; Putro, Utomo Sarjono (Journal Integration of Management Studies, 2025)
PT Perta Daya Gas (PDG), a joint venture between PT Pertamina Gas and PLN Energi Primer Indonesia, is facing strategic stagnation due to its high dependency on a single asset, CNG Plant Tambak Lorok, which contributes over 93% of total revenue and also faces contract uncertainty in 2029. This study applies a scenario planning approach to formulate forward-looking strategies that enhance PDG’s competitiveness and ensure sustainable growth amid institutional limitations and an evolving energy landscape. Using a qualitative case study method, data were collected through six semi-structured interviews with key stakeholders and triangulated with policy and corporate documents. Strategic analyses using PESTEL, Porter’s Five Forces, and VRIO frameworks identified eight key driving forces. Two critical uncertainties, strategic autonomy and PLN’s gas demand were selected to construct a 2x2 scenario matrix, resulting in four plausible futures: Championship Mode, Pivot Game, Playbook Locked, and Stuck on the Bench. From the strategic implications of each scenario, twelve strategic options were formulated and subsequently evaluated using Multi-Criteria Decision Analysis (MCDA) based on five weighted criteria: revenue potential, strategic fit, shareholder alignment, operational Feasibility, and time to implement. The evaluation revealed that three strategies, enhancing O&M efficiency, implementing lean operations, and optimizing existing contracts, demonstrated high robustness and Feasibility across all scenarios. In this context, robustness refers to a strategy’s consistent performance across multiple future scenarios, while Feasibility reflects the practicality of implementing the strategy within PDG’s current organizational and governance constraints. This research highlights how integrating scenario planning and MCDA can enhance strategic foresight, organizational resilience, and decision-making quality in navigating policy-driven energy transitions, particularly within Indonesia’s midstream gas infrastructure sector.